Kepemimpinan Berbasis Data: Bagaimana Big Data Mempengaruhi Gaya Kepemimpinan Modern - Sinurat, Bernardus; Kamila, Mutiara Cantika; Safitri, Nova; Ansori, Mochammad Isa (Innovative: Journal Of Social Science Research, 2025)
This research explores the influence of big data on modern leadership styles, where leaders are expected to have not only interpersonal skills, but also capabilities in data analysis for better decision-making. Big data has the potential to increase organisational efficiency by up to 20% by providing insights through relevant patterns and trends. However, the shift towards data-driven leadership is not without challenges; many leaders face limited analytical skills, resistance to the new culture, and ethical issues related to data privacy and bias. This research uses a Literature Review approach to understand the impact of big data in various sectors and look at how leaders can adapt. The results show that the use of big data accelerates more accurate decision-making and increases transparency in organisations, which is critical to building public trust. Nonetheless, challenges such as the need for analytical skills training and setting up adequate technological infrastructure remain. Practical recommendations include the development of data analytics training programmes and the use of advanced analytics tools to support leaders in this digital age. Overall, this research highlights the importance of big data in the transformation of leadership styles and its impact on organisational performance.